1999
DOI: 10.1023/a:1018761807225
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Persons who are homeless and mentally ill present unique challenges to service providers and human service systems. In vivo case management approaches such as assertive community treatment (ACT) have shown promise in engaging this population. This paper explores case management models employed within the ACCESS program, a five year, 18-site demonstration program enriching services for homeless persons with serious mental illness. We describe the implementation of case management with ACCESS programs and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…An encouragement design was used to evaluate the effectiveness of a systems integration intervention among participants receiving ACT for 12 months at 18 sites located in nine metropolitan areas. Although the fidelity of implementation of the ACT model varied across the study sites, fidelity scores were generally comparable to scores earned by real-world ACT programs (18,19). Further, a multisource study of the sites’ fidelity showed that all sites provided outreach, medication management, and assistance with housing and entitlements, and most also provided counseling and employment assistance (18).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…An encouragement design was used to evaluate the effectiveness of a systems integration intervention among participants receiving ACT for 12 months at 18 sites located in nine metropolitan areas. Although the fidelity of implementation of the ACT model varied across the study sites, fidelity scores were generally comparable to scores earned by real-world ACT programs (18,19). Further, a multisource study of the sites’ fidelity showed that all sites provided outreach, medication management, and assistance with housing and entitlements, and most also provided counseling and employment assistance (18).…”
Section: Methodsmentioning
confidence: 82%
“…Although the fidelity of implementation of the ACT model varied across the study sites, fidelity scores were generally comparable to scores earned by real-world ACT programs (18,19). Further, a multisource study of the sites’ fidelity showed that all sites provided outreach, medication management, and assistance with housing and entitlements, and most also provided counseling and employment assistance (18). Our study was granted exempt status by the University of Pittsburgh Institutional Review Board because we used previously collected data that had no personal identifiers.…”
Section: Methodsmentioning
confidence: 82%
“…Programme differentiation is whether critical features that distinguish the programme from the comparison condition are present or absent during implementation and participant responsiveness which is the extent to which participants are engaged by and involved in the activities and content of the programme. This study did not measure fidelity to process because the criteria for measuring fidelity to process are fundamentally difficult to quantify as they measure dynamic qualities of the intervention [74, 75] and measuring these criteria are resource-intensive [76]. In addition, in the unique population studied, assessing participants’ responsiveness, as fidelity measure would be a challenge due to their disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Szulanski and Winter [36] state that a best practice should be copied as closely as possible, in minute detail, and that adapting a successful template is a mistake. On the other hand, there is often a legitimate need to tailor a program to local circumstances and resources and to the social and cultural needs of the target population [37-39]. For example, patients in different locations have different strengths and needs and health service organizations have different goals and objectives.…”
Section: Discussionmentioning
confidence: 99%